Impedance Controller Analysis for a Two-Degrees-Of-Freedom Ankle Rehabilitation Machine with Serious Game Interactions - Oscar I. Cirilo-Piñon; Agustín Barrera-Sánchez; Cesar H. Guzmán-Valdivia; Manuel Adam-Medina; Rafael Campos-Amezcua; Andrés Blanco-Ortega; Arturo Martínez-Mata (Computation)
An ankle sprain can be caused by daily activities such as running, walking, or playing sports. In many cases, the patient’s ankle suffers severe or permanent damage that requires rehabilitation to return to its initial state. Thanks to technological advances, robotics has allowed for the development of machines that generate precise, efficient, and safe movements. In addition, these machines are manipulated by a specific control depending on the rehabilitation objective. Impedance control is used in ankle rehabilitation machines for active–resistive-type rehabilitation, where the patient participates by exerting a force on the machine repeatedly. Serious games are an example of an activity where the patient can interact with a video game while rehabilitating. Currently, most machines involving impedance control and targeted at serious gaming applications are mechanically composed of one degree of freedom, so the addition of another degree is a novelty. This paper presents simulation results comparing different impedance controls reported in the literature to determine the best option for applying a 2-DOF ankle rehabilitation machine using serious games. The results obtained are presented by comparing them according to the force applied to the rehabilitation machine (emulating the behavior of a patient). From the impedance controllers analyzed for horizontal (abduction/adduction) and vertical (dorsiflexion/plantarflexion) movements in the rehabilitation machine, it was determined that the PD control, which considers some mechanical parameters, presents a better performance. With this controller, fast and smooth angular movements are generated, while the consumption of kinetic energy is kept in a low range, proportional to the applied forces, compared to the other impedance controls analyzed.